The Effect of Liquidity, Company Age and Company Size on Earnings Quality (Studies on Property and Real Estate Sector Companies Period 2017-2019) - Retnoning Ambarwati; Feri Dwi Hastuti (Social Science Studies, 2021)
This study aims to analyze the effect of liquidity, firm age, firm size on earnings quality. The independent variables used are liquidity, company age, company size. The dependent variable is earnings quality. Population p enelitian are p ompany that stands in Real Estate Sector listed on the Indonesia Stock Exchange (BEI) Period 2017-2019. The sampling method used is the purposive sampling method with a total of 21 companies during the observation period of 3 consecutive years with 65 samples. Data analysis tools: classical assumption test method, multiple linear regression analysis test, and hypothesis testing. The hypothesis of this study is liquidity , Age Company , and Company Size partial effect on k Quality of earnings in the Real Estate Property companies listed on the Stock Exchange in 2017-2019 . The results showed that the liquidity of the firm size had no effect on earnings quality, while firm age had an effect on earnings quality. H acyl R 2 coefficient determinant ( R 2 ) shows at 0.353 or 35.3%, meaning that the liquidity factor (X1), Age Company (X2), Company Size (X3) affects the quality of earnings (Y) on the company's property and real estate listed on the IDX in 2017-2019, the remaining 64.7% is influenced by other factors not examined in this study such as profitability, audit quality, capital structure and so on.